Silver and Palladium Complexes of a Bis(benzimidazolin-2-ylidene)pyridine Pincer Ligand - Brown, David; Nealon, Gareth; Simpson, P.; Skelton, B.; Wang, Zhisen (ACS Publications, 2009)
Reaction of 2,6-bis(3-butylbenzimidazol-1-ium)pyridine dibromide with silVer oxide affords a dinuclear complex of the type [L2Ag2]2+ [L ) 2,6-bis(3-butylbenzimidazolin-2-ylidene)pyridine]. 1H NMR spectroscopic studies suggest that the dinuclear structure is also present in solution. Transmetalationof the silVer-NHC complex with PdCl2(CH3CN)2 yields a mononuclear palladium complex of the type [LPdCl]+, with a chelating C,N,C pincer ligand.